limx→无穷(x^2-5x+2/x^2+2x-3)^(2x+1)=不过他是得到lim(1+(-7x+5)/x^2+2x-3)2x+1=e^limx→无穷(-7x+5)(2x+1)/x^2+2x-3这步,想问问这步是怎么来的,是什么公式嘛?
来源:学生作业帮助网 编辑:作业帮 时间:2024/11/17 06:28:04
x)̭x6Wnר3562*t54*
5m}ifoӎ
@tj ]
m{:@lSPLGRdT ky泵Ku5o~9}A@۞5=lZt'k:cMR> +~/iVk[1XVUu+M4t
4c!R<<;hۀ9 ^l~}s.Yla@
` 8طH '
limx→无穷(x^2-5x+2/x^2+2x-3)^(2x+1)=不过他是得到lim(1+(-7x+5)/x^2+2x-3)2x+1=e^limx→无穷(-7x+5)(2x+1)/x^2+2x-3这步,想问问这步是怎么来的,是什么公式嘛?
limx→无穷(x^2-5x+2/x^2+2x-3)^(2x+1)=
不过他是得到lim(1+(-7x+5)/x^2+2x-3)2x+1=e^limx→无穷(-7x+5)(2x+1)/x^2+2x-3这步,想问问这步是怎么来的,是什么公式嘛?
limx→无穷(x^2-5x+2/x^2+2x-3)^(2x+1)=不过他是得到lim(1+(-7x+5)/x^2+2x-3)2x+1=e^limx→无穷(-7x+5)(2x+1)/x^2+2x-3这步,想问问这步是怎么来的,是什么公式嘛?
limx→无穷(x^2-5x+2/x^2+2x-3)^(2x+1)
=limx→无穷(x^2-5x+2/x^2)^(2x)
=limx→无穷(1-5/x)^(2x)
=limx→无穷(1-5/x)^[-x/5*(-10)]
=e^(-10)
limx趋近与无穷大(1+k/x)=e^k 这是公式